The invisible librarian : a librarian's guide to increasing visibility and impact - Lawton, Aoife (Waltham, MA, USA : Chandos Publishing, an imprint of Elsevier, 2016)
The invisible librarian: a librarian's guide to increasing visibility and impact provides insights into what many librarians are feeling, including questions such as "do they feel invisible?" and "How many times have they heard somebody say 'but everything is on the Internet'?" If you are a librarian struggling to find the best strategy for the future of the profession in a rapidly changing information environment, this book is for you. People don't realize that librarians make information available and not just by search engine. This book will make people think differently about librarians, making a case for their value and impact that is compelling, convincing, and credible. Given their versatility and knowledge, now is the time for librarians to become champions of the information age as they improve the visibility and impact of libraries to readers, to stakeholders, and in society. By the end of the book, librarians will have a Visibility Improvement Plan to guarantee future success.
Includes bibliographical references (pages 321-336) and index.
oif 21/01/2020
Loans
Keywords: Public services (Libraries); Librarians; Library science; Libraries--Public relations; Libraries--Marketing; Computer-assisted instruction; Educational technology; Instructional systems